Efficacy of digital picture book enhancements grounded in multimedia learning principles: Dependent on age?. (June 2023) - Li, Xuan; Bus, Adriana G.
Abstract: We designed an experiment with stratified randomization to investigate the effects of visual and auditory enhancements in digital picture books on comprehension and incidental word learning. Participants were 183 children aged 3, 4, and 5 years (81 girls and 102 boys) from childcare centers and schools in the Southwest USA. We contrasted the still-image condition (an onscreen picture book with a voice-over reading the narrative aloud) with three enhanced conditions: a digital book that included auditory and visual enhancements, only auditory enhancement, or only visual enhancement. All participants watched and listened thrice to the researcher-assigned digital picture book version within three weeks. The posttests assessed children's story comprehension and book-based vocabulary. The visual and auditory enhancements benefited children's story comprehension and book-based vocabulary. However, a version with auditory and visual enhancements was less beneficial for comprehension than versions with single (auditory or visual) enhancements, particularly in the youngest group. Highlights: The study tests the effects of enhancements in digital picture books. We did an experiment to test the effects of three repeated readings. In a sample of 183 children 3–5 years old. Visual and auditory enhancements support comprehension. However, both enhancements simultaneously less, particularly in the youngest group.